CODE SWITCHING - Halim Shanty (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2014)
This paper describes about the code switching. In multilingual society, peoples tend to use more than one language or a veriaty when they communicate to each other. They choose certain language to us in particular condition of situations. Code switching can be defined as the employment of more than one code or language in one sentence. In code switching one language may be more dominant than other. It happens when a speaker uses one language mostly than the other in a discourse. The dominant language is termed as "matrix language" while the subdominant one is "embedded language". Thus, for example the speakers of Indonesian-English code switching use Indonesian more than English, then Indonesian is the matrix language (ML) while English is the embedded language (EL).